La sobreprotección en el proceso enseñanza aprendizaje - Sigcha Cunuhay, Jesica Fabiola (2017)
The present research work, is about the overprotection in the Teaching-Learning Process, it is manifested as an exaggerated behavior, mistaken that can obstruct the development of the children; also the excessive consent presents two important problems in the education of the children, their conduct and learning. The parents live for looking after their children in such as in their care and attention, and they avoid all types of problems. We found, principally children being overprotected in first-time, parents, single mothers, and separated families and those that work full time, the same one that deprive their children of their freedom in thinking and create in them instability, nervousness, fear, low self-esteem, breaking the rules, avoids their maturity, difficulty in the development of their learning, turns their children into passive subjects, defenseless, useless and dependent. Nowadays social, technological and behavior changes have placed school and family in a new situation, where the school is in charge of making the child a social being, fomenting them with ideas, values and good behaviors from the group that they belong to, meanwhile the family is responsible for transmitting values and attitudes that are proper to the society. The overprotection reprehends in the Teaching –Learning Process, the education system depends on the confidence that the parents provide towards the teachers in their daily work that generates change in the development and process of the learner….